Body Height Estimation According to Deciduous Dental Crown Height in a Peruvian Sample of Preschool Children - Aldana Yanira Pimentel-Chalco; Kilder Maynor Carranza-Samanez; Julissa Amparo Dulanto-Vargas (Hindawi Limited, 2024)
Introduction. Odontometry and body height are distinctive biological traits, making their relationship relevant in the identification of individuals. The objective of this study was to estimate body height according to the height of the crown of deciduous teeth in Peruvian preschool children. Materials and Methods. This analytical study was applied to a calculated sample of 204 preschoolers between 3 and 5 years of age (34 per sex/age group) with fully erupted upper anterior deciduous teeth (from #53 to #63). Measurements included body height with a stadiometer (106 ± 6.56 cm; 94-123 cm) and crown height from canine to canine (3.06 mm in #62 to 8.13 mm in #53) in models with digital vernier (intraclass correlation coefficient ≥ 0.781). Linear regression models included calculation of the regression coefficient (β) to predict height based on crown height for each deciduous tooth at a significance level of P<0.05. Results. There was no correlation between body height and crown height by tooth type in the total sample (P≥0.05), but there was in a 3-year-old female in #52 (r = 0.4: moderate) and a 5-year-old female in #53 and #63 (r = 0.36-0.38: low) (P<0.05). Body height prediction equations are shown according to crown height per tooth and sex/age groups. The regressions were significant, explaining 13%-18% of 3-year-old females in #53 and #52 (1.85-1.86 cm error) and 5-year-old females in #53, #51, and #63 (4.61 at 4.63 cm error) (P<0.05). Conclusions. The odontology method using crown height of the upper anterior deciduous teeth estimated body height in Peruvian girls of 3 and 5 years of age. The teeth are resistant to traumatic forces so these could be used as a body height estimation parameter for forensic human identification.